Internet Adoption in Older Adults: Findings from the Health and Retirement Study - Macdonald, Birthe; Hülür, Gizem (Cyberpsychology, behavior and social networking, 2021)
Being able to use the Internet is becoming increasingly important in today's digitized society. Evidence suggests that older adults are at risk of being left behind by technological developments. We examined Internet adoption in older adults in relation to sociodemographic, health, cognitive, social, and personality factors. We used data from the Health and Retirement Study ( = 5,949; 61 percent women; age: = 72 years, standard deviation [ ] = 7; range = 50-105). Internet use was examined over an 8-year period. Predictors were assessed at baseline. We used a Cox proportional hazards model to examine how predictors were related to Internet adoption during the study period. Overall, 1,296 out of 5,949 participants (22 percent) reported starting to use the Internet during the study period. Our findings revealed that younger age, higher education, higher income, living with a partner, and better cognitive performance were associated with a higher likelihood of Internet adoption, whereas being Black was associated with a lower likelihood. Openness was associated with a higher likelihood of Internet adoption over the study period. Our findings add to the literature on the role of sociodemographic, cognitive, and health factors in older adults' Internet use. In addition, we show that personality also predicts older adults' Internet use.